Interdisciplinary Teamwork in Saudi Healthcare: Perspectives from Medical Professionals - Maha Msfer Alasmari; Faten Hamed Alanzi; Abdulrahman Muayjil Almutairi; Ayed Shabeb Almutairi; Mashary Fahad Alhmdane; Raed Lafi Almutairi; Adel Saad Almutairi; Saeed Saud Murayziq Almutairi; Mamdouh Shalh Moateq Al-Mutairi; Abdullah Homud Almutairi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
In today’s healthcare landscape, delivering high-quality, patient-centered care requires a coordinated effort among various medical professionals. The complexity of modern healthcare, coupled with the rise of chronic diseases and an aging population, has made interdisciplinary teamwork an indispensable component of effective healthcare delivery. Interdisciplinary teamwork involves the collaboration of healthcare professionals from different disciplines, such as physicians, nurses, pharmacists, and allied health professionals, to provide comprehensive and coordinated care for patients.